Pengaruh Pemberian Susu Kedelai (Glycine max L. Merr) Terhadap Kadar Kolesterol Total Pada Wanita Menopause (Studi Pada Ibu-Ibu Pengajian Aisyiyah) - Abdul Wahab Dalimunthe; Amelia Eka Damayanti (Universitas Muhammadiyah Sumatera Utara, 2020)
In postmenopausal women, estrogen secretion decreased due to ovarian atrophy. Increased levels of total cholesterol occur after menopause or after ovarectomy. The use of soybean phytoestrogens shows the effect of reducing lipid levels in menopausal women. This study aimed to see the effect of giving soy milk to total cholesterol levels in postmenopausal women in mothers of Aisyiyah group. Thisexperimental study used the design of one group pretest and posttest. Subjects were30 menopausal women aged 43-76 years who were given 250 mL soy milk. And datawas processed using Wilcoxon test. The mean total cholesterol level before treatmentwas 241,03 mg/dL and after treatment 224.70 mg/dL, with a difference in the averagereduction in total cholesterol levels of 16,33 mg/dL with p 0,002 (p0,005). There isan effect of giving soy milk to total cholesterol levels in menopausal women.Keywords: Total cholesterol, menopause, soymilk